Fibroblast-like synoviocytes orchestrate daily rhythmic inflammation in arthritis - Downton, P; Dickson, SH; Ray, DW; Bechtold, DA; Gibbs, JE (The Royal Society, 2024)
Rheumatoid arthritis is a chronic inflammatory disease that shows characteristic diurnal variation in symptom severity, where joint resident fibroblast-like synoviocytes (FLS) act as important mediators of arthritis pathology. We investigate the role of FLS circadian clock function in directing rhythmic joint inflammation in a murine model of inflammatory arthritis. We demonstrate FLS time-of-day-dependent gene expression is attenuated in arthritic joints, except for a subset of disease-modifying genes. The deletion of essential clock gene Bmal1 in FLS reduced susceptibility to collagen-induced arthritis but did not impact symptomatic severity in affected mice. Notably, FLS Bmal1 deletion resulted in loss of diurnal expression of disease-modulating genes across the joint, and elevated production of MMP3, a prognostic marker of joint damage in inflammatory arthritis. This work identifies the FLS circadian clock as an influential driver of daily oscillations in joint inflammation, and a potential regulator of destructive pathology in chronic inflammatory arthritis.